Evaluation of Conservation Tillage Systems and Weed Management on Yield and some Characteristic of Cucurbita pepo L. - Seyed Mortaza Shekarlu; Sasan Rezadoost; Farzad Jalili (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
This study was conducted to evaluate conservation tillage systems and weed management methods in the form of split plot design based on randomized complete blocks with 3 replications in Khoy and Maku counties in 2019-2020 crop year. The main plot included conservation tillage at Four levels including (conventional tillage, zero tillage, chisel, disc) and the sub-plot of weed management at Four levels included (herbicide use, weed-free, uncontrolled and control). The highest number of seeds (211), biological yield (7.62 t.ha-1), oil yield (83.33 kg.ha-1) and protein yield (34.6kg.ha-1) were observed in Khoy region and the lowest number of seeds (114), biological yield (1.01 t.ha-1), oil yield (19.7 kg.ha-1) and protein yield (1.66 kg.ha-1) under the influence of disc and weed-free treatment in Maku region Was. Also, the highest grain yield (828 kg.ha-1) was observed under the influence of chisel and weed-free treatments and the lowest (756 kg.ha-1) was observed in disc treatment without weed control. In general, the comparison of the average experimental treatments indicates the superiority of tillage treatment with chisel and weed management (weed-free) in Khoy region and it seems that in crop systems to maintain crop yield potential and improve integrated weed management Weeding, minimal tillage operations and weed control are recommended.